Strengthening Perceptions of Ethical Competence Among Nursing Students and Graduates - Samira Obeid PhD, MPH, RN; Michal Man PhD, RN (SAGE Publishing, 2020)
Introduction Ethical competence is part of all health-care professionals' general competence. It relates to moral issues and is based on the professionals' knowledge, skills, and attitudes for coping with ethical dilemmas. Ethics education aims to increase nursing students' and nursing graduates' ethical self-confidence. Previous research has found many gaps in ethical education content and poor understanding of how these gaps affect graduates. Objectives This study aims to evaluate an advanced education workshop held in the nursing department in Max Stern Yezreel Valley College aimed at strengthening the self-perceptions of ethical competence, to address the above gap, by raising students' self-efficacy when coping with ethical dilemmas. Methods The effectiveness of the workshop for nursing students was evaluated using the Generalized Self-Efficacy Scale and at three points in time: before the workshop, after the workshop, and after graduation. Results Statistically significant differences were found in overall self-efficacy: before the workshop (mean of 2.42), after the workshop (mean of 2.13), and for graduates (mean of 1.58) with p  < .000 on a scale ranging from 1 to 5 (1 indicating high self-efficacy). Mean scores for students' evaluation after the workshop and for graduates were 7.8 and 7.25, respectively, on a scale ranging from 1 to 10, where 10 indicates high self-efficacy. Graduates presented a high mean score regarding their ability to cope with ethical dilemmas when compared with other nurses working with them (mean of 7.4, on a scale ranging from 1 to 10). Conclusion Levels of self-efficacy with regard to coping with ethical dilemmas increased over time, suggesting that the workshop strengthened the self-perception of ethical competence for nursing students and graduates.